The epithelial-mesenchymal transition induced by transcription factor LEF-1 is independent of β-catenin - Kobayashi, Wakako (Biochem Biophys Rep, 2018)
Transcription factor lymphoid-enhancer–binding factor 1 (LEF-1) is a key molecule in the Wnt/β-catenin signaling pathway. Slug is one of the Wnt/β-catenin target genes and can induce epithelial–mesenchymal transition (EMT). Previously, we have shown that not only wild-type LEF-1 but also LEF-1 lacking the amino-terminal β-catenin–binding region can induce EMT, suggesting that LEF-1 acts independently of β-catenin. Because it has been reported that LEF-1 interacts with β-catenin outside the amino-terminal domain, namely, in the middle part of the molecule, the possible participation of β-catenin has not been formally ruled out. To determine the involvement of β-catenin in the LEF-1–induced EMT, we produced MDCK cells with a deletion of the β-catenin gene and then expressed LEF-1 in the cells. We found that LEF-1 induced EMT in those cells. In the absence of β-catenin, γ-catenin has been shown to take over the role of β-catenin. To examine this possibility, we first established MDCK cells with a double knockout of β-catenin and γ-catenin genes and then expressed LEF-1 in these cells. We found that LEF-1 can induce EMT in these cells; therefore, we conclude that neither β-catenin nor γ-catenin expression is necessary for the LEF-1–mediated induction of EMT.